RETRACTED: Infusion extraction and measurement on CT images based on computer vision and neural network - Hamad Yousif A.; Alekhina Anna; Pleshkova Tatiana; Shestakova Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001